The Impact Of Audit Findings, Audit Opinion And Size Of Government On The Level Of Local Government Corruption (Empirical Study On Regency And City In Banten Province In 2019 - 2023) - Rizki Bella Andhika Siregar; Dirvi Surya Abbas; Imam Hidayat (UNIVED Press, 2025)
Audit act as independent monitors and transparent performance assessors to overcome the information asymmetry between principal and agent, thereby reducing the risk of fraud and manipulation (in this context, corruption). Although the audit system has been implemented in the government, data from the Banten Prosecutor's Office shows that corruption cases still occur, especially in the districts and cities of Banten in 2019-2023. The purpose of this study was to determine the effect of audit findings, audit opinion, and government size on the level of local government corruption, an empirical study of regencies and cities in Banten Province in 2019-2023. This type of research uses quantitative research. The techniques used to analyze the data in this study are descriptive statistics, classical assumption tests and hypothesis testing. The number of samples used was 8 districts and cities in Banten Province in 2019-2023. From the results of t-test hypothesis testing, it is known that audit findings (X1), audit opinion (X2) and size of government (X3) have no significant effect on the level of corruption. For f-test, the significance results are audit findings (X1), audit opinion (X2) and government size (X3) have no effect simultaneously or together on the level of corruption.